Analisis Risiko Kecelakaan Kerja Dengan Metode Job Safety Analysis Pada Proyek Konstruksi - I Kadek Dony Suryadana; Anak Agung Istri Agung Sri Komaladewi; Ni Made Cyntia Utami (CV.ITTC INDONESIA, 2024)
Job Safety Analysis (JSA) is a method to identify and evaluate work steps and potential hazards to determine appropriate control measures. The ultimate goal of this research is to identify the potential for work accidents, assess the potential for work accidents, and provide risk control for existing work accidents. The results of this study found a variety of common hazards such as physical injury (puncture, scratch, pinch, fall), chemical hazards (dust inhalation, skin irritation), and mechanical hazards (slipping, falling material). In the concrete field, accident risks include being buried in soil, tripping over stones, slipping, inhaling dust, and being injured by work tools. While in the electrical field, the risks include being scratched by tools, falling from a height, being punctured by nails, and respiratory problems. The assessment of work accidents at PT Tunas Jaya in 2022 mostly shows a high risk of work accidents and repeatedly occurs. In addition, the factors affecting work accidents were analysed using the Job Safety Analysis (JSA) method. recommendations can be given to control the risk of work accidents in the next construction project at PT Tunas Jaya by updating the existing Standard Operating Procedures (SOP), adjusted to current field conditions.